Pengaruh Fee Audit, Audit Delay, Dan Ukuran Perusahaan Klien Terhadap Kualitas Audit: Studi Kasus Pada Perusahaan Sektor Perindustrian Yang Terdaftar Di Bursa Efek Indonesia (bei) Tahun 2018-2022 - Azzam, Afghan Adillah; Farida, Ajeng Luthfiyatul (eProceedings of Management, 2024)
Audit quality is the totality of auditor services that are important for finding violations, correcting financial reports,and ensuring accurate accounting information. This study attempts to ascertain the impact of audit fees, audit delay,and client business size on audit quality in firms in the industrial sector that are listed between 2018-2022 on the IDX.This study employs a quantitative approach of secondary data type using the IBM SPSS version 26 application to testthe research hypothesis. Using purposive sampling, 37 firms or 185 data from industrial companies written on theIDX between 2018 and 2022 served as the study's samples. The total data after removing outliers is 170 data. Thisresearch was analyzed using descriptive statistics also logistic regression. The study's findings suggest that the sizeof the client firm, audit costs, and audit delay all have an impact on audit quality. In addition, audit fees also clientcompany size have a positive influence on audit quality. Meanwhile, audit delay has no influence on audit quality.The contribution of this study is that audit fees and client company size are positive determinants of audit quality inindustrial sector companies. Recommendations for further study is to change the independent variables that have noinfluence on audit quality with different proxies, periods and research objects. Keywords-audit quality, audit fee, audit delay, client company size.